2010
DOI: 10.1590/s0100-83582010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Green ear yield and grain yield of maize cultivars in competition with weeds

Abstract: -The reduction in herbicide use is one of the greatest interests for modern agriculture and several alternatives are being investigated with this objective, including the adoption of cultivars that suppress weeds. The objective of this study was to verify if maize cultivars develop differently, in competition with weeds, to produce green ears and grain. Randomized complete block design was used, with split-plots and five replications. Cultivars DKB 390, DKB 466, DKB 350, AG 7000, AG 7575 and Master, were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Norris (1992) observed a reduction of sugar beet (Beta vulgaris L.) root with the existence of weed as Barnyardgrass (Echinochloa crus-galli L.). Additionally, Silva et al (2010;2011) reported a reduction of corn root biomass without weeding (hoeing). The observed root reduction in NT could be caused by the delayed early growth associated with the competition against weeds for resource acquisition.…”
Section: Corn Roots Affected By Tillage Practicementioning
confidence: 99%
“…Norris (1992) observed a reduction of sugar beet (Beta vulgaris L.) root with the existence of weed as Barnyardgrass (Echinochloa crus-galli L.). Additionally, Silva et al (2010;2011) reported a reduction of corn root biomass without weeding (hoeing). The observed root reduction in NT could be caused by the delayed early growth associated with the competition against weeds for resource acquisition.…”
Section: Corn Roots Affected By Tillage Practicementioning
confidence: 99%
“…The RDM was validated against measurements from a field release of Lycopodium spores ( cms -1 ) in a maize canopy (Gleicher et al, 2014), which is the same study used for comparison in Figure 2a. Gleicher et al (2014) report m s -1 , m, The characteristic vegetation length scale is the leaf width, m (Silva et al, 2012). Gleicher released spores from a single pole at three source heights ( ) and captured spores using a grid of 9 poles, with 5 rotorods per pole ( , , m).…”
Section: Validation Using Field Data From Maize Canopymentioning
confidence: 99%
“…Production of green cobs is more profitable than grain production, and it is harvested in a short period of time as compared to the grain harvesting time [9]. Green cob is mainly produced for human consumption, either as a fresh cob, as a boiled or roasted condition, or as a processed product used as an ingredient in cakes, ice creams, and a number of other foods [9,10]. Green cob is suitable for fresh consumption due to its sweet and delicious taste.…”
Section: Introductionmentioning
confidence: 99%